Effects of adipose tissue extracellular matrix components on body fat distribution and insulin sensitivity in black and white South African women - Kotzé-Hörstmann, Liske (Department of Human Biology, 2019)
The global burden of non-communicable diseases (NCD’s) is unacceptably high and disproportionately affects developing countries such as South Africa (SA). Black SA women have a higher prevalence of obesity and a greater associated risk for developing metabolic diseases (such as type 2 diabetes mellitus) than their white counterparts. An improved understanding of the ethnic-specific mechanisms underlying the increased risk of T2DM in black SA women is needed to inform future studies aimed at reducing the prevalence of this diseases. One of the major determinants of insulin resistance is android/central body fat partitioning, with visceral adipose tissue (VAT) enlargement, in particular, being closely associated with increased risk. Conversely, lower-body fat accumulation is considered to be protective. However, these relationships between body fat distribution and its metabolic effects are altered by ethnicity. Black SA women have less abdominal and greater gluteal-femoral subcutaneous adipose tissue (SAT) but are more insulin resistant compared to BMI- and waist circumference-matched white SA women. A similar profile has been described in black African-American women. The reduced protective effect of peripheral fat distribution in black women remains to be understood. The primary aim of this thesis was positioned within the context of adipose tissue expandability hypothesis, and aimed to examine the hypothesis that differences in SAT extracellular matrix (ECM)- and hypoxia-related gene expression and their ethnic specific associations with body composition and insulin sensitivity may explain, in part, the higher rates of insulin resistance in black compared to white South African women. Therefore, it was hypothesized that, as a consequence of increased adipose tissue hypertrophy in the gluteal depot of obese black compared to obese white women, gluteal SAT adipose tissue hypoxia and ECM component gene expression is higher in black compared to white women, and associates with their reduced insulin sensitivity (SI) and higher insulin response. In order to address this hypothesis, four research studies were designed. The first study (Chapter 3) in this thesis aimed to compare depot-specific (abdominal vs. gluteal) expression of hypoxia and ECM genes in normal-weight and obese black and white women, and to examine the ethnic-specific associations between these genes and body composition, measures of insulin sensitivity and secretion and inflammatory gene expression in black and white SA women by using a gene expression (Reverse transcription polymerase chain reaction (RT-PCR)) analysis. This thesis showed for the first time that hypoxia inducible factor 1 (HIF-1α), collagen type V α1 (Col5A1) and type VI α1 (COL6A1) gene expression were higher in the gluteal, but not the abdominal SAT depots, of black compared to white women, and associated with reduced insulin sensitivity in black women only. The expression of the hypoxia and ECM genes associated with inflammatory gene expression in both the gluteal and abdominal SAT depots of black women, whereas the expression of these genes associated with the inflammatory gene expression mostly in the abdominal SAT depots of white women. The second study (Chapter 4) tests the hypothesis that higher hypoxia and ECM related gene expression would associate with higher central fat mass accumulation in black women and that the expression of these genes may be associated with changes in the measures of insulin sensitivity in black and white women. Thus, this longitudinal study aimed to determine whether changes in body composition and insulin sensitivity variables over a 5 year follow-up period associated with variations in hypoxia and ECM related gene expression in the gluteal SAT of black and white women. Over the 5-year follow-up period, increased body fat mass in white women associated with increased PPARγ mRNA expression whereas increased body fat mass in black women associated with lower COL5A1 expression. Furthermore, HIF-1α, and COL6A1 expression correlated positively with the change in fasting insulin concentrations in black but not in white women. It is not clear whether high circulating insulin may directly increase HIF-1α expression and contribute to the formation of excess ECM, or whether increased insulin may simply be a concomitant downstream effect of increased insulin resistance, as a consequence of increased fibrosis and the generation of inflammation. By using a cell culture based study, the third study in this thesis (chapter 5), investigated the effects of increasing insulin concentrations on the expression of hypoxia and ECM related genes under normoxic and hypoxic conditions in mature 3T3-L1 adipocytes. It was found that insulin and hypoxia treatment significantly elevated HIF-1α mRNA and protein levels but that the observed effects were not additive. Further, hypoxia, but not insulin treatment, increased the expression of Col5a1 and Col6a1 protein but not mRNA levels in mature 3T3-L1 adipocytes. By using a genotyping analysis, the fourth study (Chapter 6) aimed to determine whether variants within two ECM component gene polymorphisms, collagen type 5α1 (COL5A1) rs12722 (C/T) and type 6α1 (COL6A1) rs35796750 (C/T) associates with body fat distribution and insulin resistance in black and white women. Allele and genotype distributions of the COL5A1 rs12722 and COL6A1 rs35796750 polymorphisms, as well as body fat distribution were significantly different between black and white women, the T- variant of the COL5A1 rs12722 polymorphism was associated with significantly less central fat mass, characterised by a smaller waist circumference and lower VAT, and this effect was independent of ethnicity. In addition, T- variant of the COL5A1 rs12722 polymorphism was associated with lower fasted insulin concentrations and HOMA-IR in white but not in black women. In contrast, no genotype associations between COL6A1 rs35796750 and any of the body fat mass, its distribution and insulin resistance measures in black or white women were reported. This thesis used a hypothesis driven approach to provide preliminary evidence that the gluteal depot of obese black women has higher expression of hypoxia and ECM genes compared to that of obese white women and provides novel insight into the apparent paradox of reduced insulin sensitivity despite lower VAT and greater peripheral SAT accumulation in black compared to white women. An improved understanding of the ethnic-specific mechanisms underlying the increased risk of T2DM in black SA women will enable the development of cost-effective preventative care strategies within the South African demographic